Novel geometric design of thermoelectric leg based on 3D printing for radioisotope thermoelectric generator. (25th July 2022) - Bian, Mingxin; Xu, Zhiheng; Meng, Caifeng; Zhao, Huanyu; Tang, Xiaobin
Highlights: A design concept of geometry of 3D printing thermoelectric (TE) legs is proposed. Two TE legs with geometrical shapes of helix and spoke are designed. The improvement effect of geometric design on output performance of TE legs is analyzed. 3D printed TE modules with special shapes exhibit outputs of more than 30% increments. Abstract: To meet the power supply development needs of electronic devices in spacecraft, the optimized design and fabrication of geometric configuration of thermoelectric (TE) legs to increase the power output of radioisotope thermoelectric generators are proposed. The principle of performance enhancement is the increase of heat dissipation on the increased side area, which is analyzed according to Fourier's law. Helix-shaped and spoke-shaped TE legs with special geometrical shapes are proposed and fabricated by 3D printing technology. The geometric design makes the TE legs produce a larger temperature difference and inevitably brings about an increase in resistance. Variation of TE legs' output performance with the geometrical parameters is analyzed based on the finite element method. Results show that the helix-shaped TE legs with the appropriate geometrical parameters can produce maximum output power of 2.78 mW, which are 2.55 times of the traditional cylinder-shaped TE legs with the same mass. And the spoke-shaped TE legs can produce maximum output power of 2.28 mW, which are 2.09 times of the traditional cylinder-shaped TE legs. Nine TE legs with special shapes and sixteen with traditional shapes are integrated into the same space (16.5 mm × 16.5 mm). The results show that the combination of TE legs with special shapes produce a higher power density, more than 66%–98% compared with traditional shapes due to lighter mass. TE modules with different shapes are fabricated by direct-writing 3D printing technology, and their output performances are tested. TE modules with special shapes exhibit greater open-circuit voltage and output power than the traditional shapes, which are consistent with the simulation results. The simulation and experimental results indicate that the geometric design of TE legs with larger side areas can improve the output performance of TE devices. This design concept of optimizing the geometry to increase the temperature difference can be applied to thermoelectric generators under the condition of natural heat dissipation to improve power output and heat dissipation, and reduce weight.